KARAKTERISTIK POLA AGROFORESTRI MASYARAKAT DI SEKITAR HUTAN DESA NAMO KECAMATAN KULAWI KABUPATEN SIGI - Tjatjo, Nurmasita T. (JSTT, 2015)
In Indonesia, land conversion as the development of construction is often a discussion at the community level. Land use, can lead to limited land to the community in meeting food needs. It is possible could lead to social problems in the community. Referring to the matters mentioned above,Â needed for an innovative solution, in order to optimize land use and increase people's incomes. One solution is to conduct integrated farming systems such as agroforestry. This research was conducted in the village of Namo, District Kulawi, Sigi Regency in Central Sulawesi Province. The location is based on the consideration that in the village of Namo community to implement a land agroforestry in his garden. This study was conducted over three months, from May to July 2014. The Respondent is done by purposive sampling. Data collected by interview and field observation. In-depth interviews by using interview guide and questionnaire. It also uses a questionnaire-based New Environmental Paradigm (NEP). This method is used to analyze the orientation of agroforestry-based land management, based on the criteria of value of individual, social, and environmental. The survey results revealed that, the characteristics of agroforestry in Sub Kulawi Sigi is simple agroforestry. The community motivation is this pattern guarantees and repair needs of food, as well as having a very close relationship with the local socio-cultural because it has been practiced for generations by the community. This is supported by the results of the analysis in the Social Value category (altruistic).